A Reputation Held Hostage? Commercial Mug Shot Web sites and the Trade in Digital Shame. Issue 4 (2nd October 2017) - Wesner, Kearston L.
Abstract : A cottage industry has flourished recently by engaging in philosophical extortion through the exploitation of open records laws. Various commercial Web sites obtain and publish publicly available mug shots, the booking photographs required of arrested individuals. These mug shots are elevated to the top of search results and can damage reputations and employment prospects. The Web sites then trade on the humiliation by offering to remove the photographs for a fee, subverting the intent of open records laws by monetizing information removal. In 2013, a right-of-publicity lawsuit filed against a handful of Web sites yielded a flurry of news articles that brought the issue to the public's attention. Since then, fourteen states have enacted laws targeting the Web sites' business practices. This article analyzes both the applicability of the right-of-publicity claim and the constitutionality of the state laws, ultimately advocating that states adopt narrow laws limiting the business practices of these particular Web sites, a solution that balances both openness and privacy concerns.